Consumo de água e eficiência hídrica de bovinos de corte em ambiente tropical - Matarim, Danielle Leal (2020)
First, voluntary water consumption data of 181 Nellore bulls were used to identify the main factors that influence water intake. Measurements of body weight of animals (BW), dry matter intake (DMI) and thermal environment variables, in southeastern Brazil during the winter months, were related to water consumption by regression analysis. The characteristics with the highest correlations with water intake were used in the selected regression analysis to create a water intake prediction equation. The variables that most influence water intake (WI) are dry matter intake (DMI), metabolic body weight (MBW), followed by relative humidity (RH) and minimum temperature. From these data, an equation was created, WI = 4.719 + 0.979 x DMI + 0.123 x MBW - 0.195 x Tmin - 0.079 x RH, R2 = 0.26 (P <0.001). It shows that 74% of the variation in water intake by bulls was not explained by variations in the equation, the hypothesis of individual variation between animals was raised. Thus, no second study aimed to propose water efficiency measures for cattle in feedlots and to evaluate a relationship between these measures and performance data. Data from 220 Nellore bulls from 10 to 24 months of age in southeastern Brazil were used. Data on water intake (WI), dry matter intake (DMI), body weight, average daily gain (ADG) were collected. Water conversion (WC) and residual water intake (RWI) were calculated, similar to the food efficiency indexes. RWI is based on an estimate of consumption projected from metabolic live weight and ADG. The most efficient animals (RWI-) also presented negative residual feed intake (RFI), less water intake and better water conversion rates. The less efficient animals (RWI +) consumed more water, but presented DMI and ADG similar to the more efficient animals, in most of the analyzed tests. RWI did not correlate with ADG and metabolic body weight, when analyzing all animals and the most efficient. The correlation between RWI and residual feed intake (RFI) was positive (0.40), and it was registered that animals with greater water efficiency also proved to be the most efficient in the use of the food consumed. The selection for RWI for more efficient animals should not alter the weight gain of young Nellore bulls.